Smart measurement revolution using long range technology and HLW8012 sensor integration - Isminarti Isminarti; Nanang Roni Wibowo; Asminar Asminar; Mohamad Ilyas Abas; Muhammad Ali Chandra; Nur Azhary Iriawan Eka Putra; Widya Wisanty; Fauziah Fauziah; Deny Wiria Nugraha; Chaira Saidah Yusrie (Bulletin of Electrical Engineering and Informatics, 2026)
Long range (LoRa) has advantages compared to other communication systems such as power line control (PLC), narrowband internet of things (NB-IoT), and Sigfox. The advantage of low power consumption is the implementation and reliability of LoRa communication systems across all segments of smart grid (SG) and home automation applications. Parameters of the reliability of the communication system can also be seen from the maximum distance, signal strength, and network quality in indoor and outdoor conditions as well as different heights and levels of signal collisions when transmitted. This study aims to utilize unlicensed LoRa Shield SX1276 on the 915 MHz frequency spectrum for SG communication networks to monitor messages in the form of current, voltage, and power factor using the HLW8012 sensor. This research produces a complete LoRa communication system monitoring product according to the information needed by the user.